The reality of applying activities to devolop the sensorial-kinsthetic perception for kindergarten child - Mahdi , Azedine; Marghsi , Amina; S'eghir, i Bilal (sports creativity, 2025)
he aim of the current research is to identify the reality of applying activities to develop the Sensory-kinesthetic Perception for a kindergarten child, In addition to the detection of obstacles to the application of The sensory-kinesthetic Perception activities. The researcher relied on the descriptive method by distributing electronic questionnaires via the internet on an intentional sample of 30 female teachers in some kindergartens in Setif City through social media. The results show that there is a significant lack of application of perceptual-kinesthetic activities, the formation that the teachers received is insufficient to develop perception abilities. Sensory-motor education programs lack activities that develop perception abilities, in addition to the lack of means and the lack of adequate infrastructure